Mitochondria and Fungal Pathogenesis: Drug Tolerance, Virulence, and Potential for Antifungal Therapy - Shingu-Vazquez, Miguel (American Society for Microbiology, 2011)
Recently, mitochondria have been identified as important contributors to the virulence and drug tolerance of human fungal pathogens. In different scenarios, either hypo- or hypervirulence can result from changes in mitochondrial function. Similarly, specific mitochondrial mutations lead to either sensitivity or resistance to antifungal drugs. Here, we provide a synthesis of this emerging field, proposing that mitochondrial function in membrane lipid homeostasis is the common denominator underlying the observed effects of mitochondria in drug tolerance (both sensitivity and resistance). We discuss how the contrasting effects of mitochondrial dysfunction on fungal drug tolerance and virulence could be explained and the potential for targeting mitochondrial factors for future antifungal drug development.